Evaluación de la obtención de bioetanol partiendo de la fermentación de los azúcares concentrados en las bebidas gaseosas carbonatadas vencidas por medio de Saccharomyces cerevisiae (2019)
The purpose of this project is to obtain bioethanol from the fermentation of concentrated sugars in carbonated soft drinks expired by means of Saccharomyces cerevisiae, which is carried out through experimental research. Nutrients (carbon, nitrogen, phosphorus, potassium, sulphur, magnesium and calcium), ascorbic acid (vitamin C) and defeated carbonated soft drink are selected as raw materials. Before carrying out the fermentation process, the expired carbonated soft drink is characterized, where the contraction of the preservative (sodium benzoate) is quantified by means of HPLC chromatography, the amount of sugars present by means of Brix degrees (ºBx), the volume of carbonation, the density and the potential of hydrogen (pH). The sodium benzoate present in defeated carbonated soft drinks prevents the growth of moulds and yeasts, affecting the bioethanol fermentation process. For the conditioning of the raw material, the sodium benzoate is reacted with ascorbic acid, producing sodium ascorbate, benzene and carbon dioxide, by means of a simple distillation the benzene is removed, eliminating the aromatic functional group present in the raw material.